Witchcraft : a Very Short Introduction. - Gaskill, Malcolm (Very short introductions., 2010)
Witchcraft is a subject that fascinates us all, and everyone knows what a witch is - or do they? From childhood most of us develop a sense of the mysterious, malign person, usually an old woman. Historically, too, we recognize witch-hunting as a feature of pre-modern societies. But why do witches still feature so heavily in our cultures and consciousness? From Halloween to superstitions, and literary references such as Faust and even Harry Potter, witches still feature heavily inour society. In this Very Short Introduction Malcolm Gaskill challenges all of this, and argues that what we think w.